2021
DOI: 10.1111/vec.13064
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of trauma sustained by civilian dogs and deployed military working dogs

Abstract: Objective: To compare the prevalence of types of trauma, mechanisms of injury, and outcomes among military working dogs (MWDs), operational canines (OpK9s), and civilian dogs (CDs) that sustained traumatic injury.Design: Retrospective descriptive analysis. Animals:One hundred and ninety-three cases of MWD trauma, 26,099 cases of CD trauma, 35 cases of OpK9 trauma. Interventions: None.Measurements and main results: Medical records of MWDs that incurred trauma while deployed to the Middle East were identified, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…Multiple projects utilizing the Vet-COT trauma registry have been published to date. [10][11][12][13][14][15][16][17][18] Additionally, the trauma registry provides trauma centers with information that can…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple projects utilizing the Vet-COT trauma registry have been published to date. [10][11][12][13][14][15][16][17][18] Additionally, the trauma registry provides trauma centers with information that can…”
Section: Resultsmentioning
confidence: 99%
“…At the time of writing, 17 projects have been approved to utilize registry data, over 20 abstracts presented at local, national, and international conferences, and many manuscripts have been published (n = 8) or accepted for publication (n = 4). [10][11][12][13][14][15][16][17][18] Based on feedback from VTC leads, data entry personnel (DEP), Vet-COT conference attendees, and clinical researchers utilizing trauma registry data, an updated version (2.0) of the trauma registry's data dictionary was implemented on April 1, 2017. These modifications were targeted to improve data quality, streamline data entry processes, reduce "other" categories, and expand patient data being collected for subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interesting results were obtained in the works of P. Another study (Edwards et al, 2021) compared the prevalence of injury types among military working, operational, and civilian dogs (193, 35, and 20,699 records, respectively) showed that all groups showed similar trends in injury type. Penetrating injuries were the most common, followed by blunt injuries for civilian and operational dogs.…”
Section: Figure 6 Traumatic Lesions Of Service Dogs Of Ukrainementioning
confidence: 98%
“…It is accepted that primary care of critically injured dogs on the battlefield is administered by deployed human healthcare providers ( 2 , 3 ) and there are formal reports of military medics rendering prehospital care to MWDs ( 4 , 5 ). Due to their invaluable contribution to military operations, the money invested in their training and the strong bond with their handlers, the expectation by the U.S. military is that MWDs receive the same level of care as their human counterparts ( 2 ).…”
Section: Introductionmentioning
confidence: 99%